Parametric studies of the pyramidal microwave absorber using rice husk - Nornikman, Hassan; Fareq, Malek, Dr.; Soh, Ping Jack; Azremi, Abdullah Al Hadi; Wee, Fwen Hoon; Hasnain, A. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://www.jpier.org/PIER/